Chrysomelidae (Coleoptera) types in the Royal Museum of Scotland Collection - Staines, C. L.; Whittington, Andrew E. (Zootaxa, 2003)
The types of twenty-three Chrysomelidae species in the Royal Museum of Scotland Collection are documented. Syntypes of Cassida flavicornis Olivier, Cassida guttata Olivier, Cassida humeralis Olivier, Cassida multipunctata Olivier, Cassida variolosa Olivier, Chrysomela atra Olivier, Chrysomela erythrocephala Olivier, Chrysomela ignita Olivier, Chrysomela lepida Olivier, Chrysomela variabilis spartii Olivier, Clytra floralis Olivier, Clytra paradoxa Olivier, Colaspis chrysis Olivier, Colaspis smaragdula Olivier, Donacia vittata Olivier, Doryphora angulata Stål, Galeruca coerulea Olivier, G. plebeja Olivier, Hispa maculata Olivier, H. scutellaris Olivier, Paropsis atomaria Olivier, Sagra splendida Olivier, and the lectotype of Chrysomela quadriguttata Olivier are present.